O-021 Flow Diversion in Ruptured Intracranial Aneurysms: A Systematic Review. (29th July 2016) - Madaelil, T; Moran, C; Cross, D; Kansagra, A
Abstract : Background and purpose: Flow diversion is an established technique to treat unruptured intracranial aneurysms not amenable to standard endovascular or microsurgical techniques. The suitability of flow diverting devices (FDD) to treat ruptured aneurysms is less clear. Materials and methods: An in-depth search of multiple electronic publication databases was performed for reports describing ruptured intracranial aneurysms treated by flow diversion. Clinical and radiological characteristics, interventional details, and outcomes were pooled and analyzed in aggregate. Results: The pooled cohort comprised of 126 patients with a mean age of 52.6 ± 12.5 years. Mean Hunt Hess/World Federation of Neurosurgical Societies grading scale at presentation was 2.2 ± 1.2. Treated aneurysms were located in the anterior circulation in 64% (81/126) cases and 36% (45/126) in the posterior circulation. Five distinct aneurysm morphologies were present, including dissecting (28%, 35/125), fusiform (9.6%, 12/125), giant (3.2%, 4/125), blister (37.6%, 47/125), and saccular (21.6%, 27/125) types. Favorable clinical outcome (defined as Modified Rankin Scale (mRS) = 0−2 or Glasgow Outcome Scale (GOS) = 4−5) was achieved in 81.5% (101/124) of treated patients. Unfavorable clinic outcome (defined by mRS = 3−6 or GOS = 1−3) occurred in 18.5% (23/124) of patients. Clinically significant hemorrhagic complications occurred in 5.5% (7/126) of cases, the majority of which were due to aneurysm re-rupture (4.8%; 6/126). Aneurysm size greater than 2cm was associated with a greater risk of re-rupture when compared to aneurysms smaller than 2 cm (p = 0.001). Aneurysm size greater than 7 mm was associated with more unfavorable clinical outcomes (p = 0.03). Conclusion: For ruptured aneurysms not amenable to other treatment strategies, the use of flow diversion may allow for reasonably high rates of good clinical outcomes, particularly in small aneurysms. There was a risk of re-rupture in these aneurysms, especially those larger than 2 cm. Disclosures: T. Madaelil: None. C. Moran: 2; C; Medtronic Neurovascular. D. Cross: None. A. Kansagra: None.